A Study on the Implementation of Project Based Learning in Writing Lesson - Nirma Nirma; Konder Manurung; Budi Budi (JURNAL BANUA OGE TADULAKO, 2023)
The objective of this study is to describe and analyze the findings of the previous studies regarding the implementation of Project-Based Learning in Teaching writing classes. This study was conducted qualitatively through Library Research Design. Project-Based Learning is the proposed technique to generate ideas in the paper. Implementing Project-Based Learning in writing classes affects the students' writing achievement. The previous studies analyzed here were taken from the ones conducted in 2010-2020. The levels of the previous studies are from junior high school level to university level. The result of the content analysis showed that implementing Project-Based Learning helped the students improve their writing, especially in content, organization, vocabulary, mechanics, and grammar. Furthermore, all previous studies imply that implementing Project-Based Learning provides students with several significant. They are: (1) simple, quick, and flexible in collecting information; (2) it allows the students to explore their background knowledge; (3) provides the students with broad opportunity; and (4) they allow the students to think freely and write as many ideas as possible. In conclusion, the students were stimulated to improve their writing skills and ability because of the technique's benefits. Also, the students were helped to avoid stress during the teaching and Learning.